Sosialisasi Metode Ceramah Tentang Haid Dismenorea Terhadap Upaya Meningkatkan Pengetahuan Siswi Di SMP Negeri 1 Grogol Sukoharjo Socialization Methods Lectures About Menstruation Dysmenorrhoea Efforts to Improve Students Knowledge In SMP Negeri 1 Grogo - Nuri Tri Rahmawati; Susi Endrawati (Indonesian Journal on Medical Science, 2015)
Abstract: Young women who reach adulthood will experience menstruation (periods), the periodic and cyclic bleeding from the uterus, accompanied by the release (desquamation) endometrium. Menstruation experienced by young women sometimes cause problems, namely disminorea. Disminorea a gynecological problem, ie stiffness or spasms at the bottom of the abdomen that occurs in time before menstruation. With the onset of menstrual symptoms heaviness in the stage and pain that can interfere with learning activities, and indirectly affects the productivity and quality of life of adolescents. Lecture method can improve the knowledge about menstruation dysmenorrhea terms of cognitive learning outcomes and attitudes / affective students. This research is Kuantitatif croos sectional that is made up of two cycles, each cycle has four stages. Theyare planning, action, observation and reflection. The subjects of the study are female students class 8H and 8I. The data obtained through interviews, affective, questionnaires, and cognitive tests. The technique of data analysis is descriptive qualitative. Showed that socialization with lecture method 1) can increase the result of cognitive learning 71,3% in the first cycle to 83,7% in the second cycle or the percentage of completeness classroom 76% in the first cycle to 94% in the second cycle. 2) Can improve students affective learning outcomes. Data views of the percentage of achievement 77% in the first cycle to 80% in the second cycle. Lecture sociable about menistry dismenorhea can increase student knowledge class 8H and 8I SMP N 1 Grogol Sukoharjo. Keyword: Cross-sectional, dysmenorrhea, cognitive, affectiv  Abstrak: Remaja putri yang menginjak dewasa akan mengalami haid. Haid yang dialami remaja wanita terkadang menimbulkan masalah, yaitu disminorea. Gejala haid dengan timbulnya rasa berat di panggung dan nyeri yang dapat mengganggu aktivitas belajar, dan secara tidak langsung berdampak pada produktivitas dan kualitas hidup remaja. Metode ceramah dapat meningkatkan pengetahuan tentang haid dismenorea ditinjau dari hasil belajar kognitif  dan sikap/afektif siswa. Penelitian ini merupakan penelitian kuantitatif cross-sectional. Penelitian ini terdiri dua siklus. Setiap siklus terdapat 4 tahap yang terdiri perencanaan, tindakan, pengamatan, dan refleksi. Subyek penelitian siswi kelas 8H dan 8I. Data diperoleh melalui wawancara tidak terstuktur, angket afektif dan test kognitif. Teknik Analisis data yang digunakan adalah deskriptif kualitatif. Pemberian sosialisasi metode ceramah dapat meningkatkan hasil belajar kognitif dengan ketercapaian 71.3% disiklus I menjadi 83.7% pada siklus II, atau dengan persentase ketuntasan kelas 76% pada siklus I menjadi 94% pada siklus II, 2) dapat meningkatkan hasil belajar afektif siswi. Data dilihat dari persentase ketercapaian 77% disiklus I menjadi 80% pada siklus II. Metode ceramah tentang haid dismenorea dapat meningkatkan pengetahuan kognitif dan afektif siswi kelas 8H dan 8I di SMP Negeri 1 Grogol Sukoharjo. Kata Kunci:  Cross-sectional, Dismenorea, Kognitif, Afektif